2000
DOI: 10.1093/emboj/19.21.5611
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a covalently stabilized complex of a human alphabeta T-cell receptor, influenza HA peptide and MHC class II molecule, HLA-DR1

Abstract: An αβ T‐cell receptor (αβTCR)/hemagglutinin (HA) peptide/human leukocyte antigen (HLA)‐DR1 complex was stabilized by flexibly linking the HA peptide with the human HA1.7 αβTCR, to increase the local concentration of the interacting proteins once the peptide has been loaded onto the major histocompatibility complex (MHC) molecule. The structure of the complex, determined by X‐ray crystallography, has a binding mode similar to that of the human B7 αβTCR on a pMHCI molecule. Twelve of the 15 MHC residues contacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
258
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(267 citation statements)
references
References 74 publications
6
258
3
Order By: Relevance
“…25 For orientation purposes, MHC II residues interacting with peptide as well as certain T-cell receptor (TCR) contact residues are shown as evidenced from two human MHC class IIpeptide-TCR complexes, where the same TCR molecule interacts with an identical microbial peptide in identical registers in two slightly different human MHC class II molecules (DR1 and DR4). 26,27 All DQA1*0301-bearing molecules (that is, DQ8cis and DQ2trans) have an intensely positively charged region in the vicinity of a48-54, with three Arg residues on the surface (Arg49, Arg50 and Arg53) and another one (Arg52) at the bottom of pocket 1. It is apparent that these three arginines on the surface of pocket 1 would contribute vastly to the attraction of a negatively charged p1 acidic residue that HLA-DQ8 homozygosity and heterozygosity in type 1 diabetes P Eerligh et al would eventually be anchored and detained tightly via these interactions.…”
Section: Resultsmentioning
confidence: 99%
“…25 For orientation purposes, MHC II residues interacting with peptide as well as certain T-cell receptor (TCR) contact residues are shown as evidenced from two human MHC class IIpeptide-TCR complexes, where the same TCR molecule interacts with an identical microbial peptide in identical registers in two slightly different human MHC class II molecules (DR1 and DR4). 26,27 All DQA1*0301-bearing molecules (that is, DQ8cis and DQ2trans) have an intensely positively charged region in the vicinity of a48-54, with three Arg residues on the surface (Arg49, Arg50 and Arg53) and another one (Arg52) at the bottom of pocket 1. It is apparent that these three arginines on the surface of pocket 1 would contribute vastly to the attraction of a negatively charged p1 acidic residue that HLA-DQ8 homozygosity and heterozygosity in type 1 diabetes P Eerligh et al would eventually be anchored and detained tightly via these interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of the 3K peptide bound to IA b reveals five upwardly pointing amino acids as potential candidates for recognition by the ␣␤ T cell antigen receptors (TCR): the p-1Glu, p2Gln, p3Lys, p5Lys, and p8Lys. The side chains of these amino acids are at least partially exposed on the molecule surface and fall within the footprints seen of the ␣␤TCRs on other MHCII͞peptide complexes (51,52). To test whether these are indeed important for recognition, we synthesized a set of mutant peptides in which each of these amino acids was mutated to Ala.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table III, MK20.2 had the same V␤3.1 usage as did HA1.7, and it was reported that V␤3.1 was predominantly expressed in HA 306 -318 -specific TCRs which preferred P8K of HA 306 -318 (42). Molecular modeling (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Although the two TCRs represented a distinct specificity at relative positions 3, 5, 7, or 8 of the peptides, SA32.5 TCR and MK20.2 TCR represented similar preferences for certain amino acids at some positions. For example, at relative position 1, both TCR tolerate phenylalanine, methionine, leucine, isoleucine, valine, and cysteine; at relative position 4 they tolerate leucine, methionine, glutamine, (42), interactions between residues that provide TCR-DR binding sites between ␣-helical structure of the DR␣ chain and the CDR2 region of HA1.7 TCR are lined with dotted doublet lines. Electrostatic interactions between P8K of HA (peptides 306 -318) and the CDR region of HA1.7 are indicated by solid doublet lines.…”
Section: Discussionmentioning
confidence: 99%